(untitled) (Plant Tissue Culture and Biotechnology, 2025)
Selected anthers from seven brinjal germplasm namely; Anjalee, Padagoda, EGH-5, EGH-13, EGH-16, V-5, and 8104 were cultured on MS medium containing different hormonal supplements for callus induction and in vitro regeneration. Various hormonal treatments (T1 to T4) for callus induction consisted 1.0 mg/l Kn and 2.0 mg/l BAP with different concentrations (1, 3, 5 and 0 mg/l) of NAA. The highest percentage of callus induction (83.33 ± 16.67, p <0.05) was obtained in T2 from the hybrid germplasm EGH-13. Significantly the highest percentage of root formation (83.33 ± 16.67, p <0.05) was obtained on 1 mg/l BAP from EGH-13. MS supplemented with 1 mg/l BAP was found to produce shoot (6.67 ± 6.67, (p <0.05) only for germplasm Padagoda. All other germplasm failed to produced shoots on any medium having different combination of hormonal supplements. Plant Tissue Cult. & Biotech. 34(2): 165-171, 2024 (December)